Effect of Leverage, Growth, Firm Size, Dividend Policy, and Interest Rate on Company Value - Yudha Pradana, Ivan (Dinasti Publisher, 2021)
The purpose of this study is to determine influence of Leverage, Growth, Firm Size, Dividend Policy and Interest rate on the value of the company of construction and building sub-sector companies listed on the Indonesia Stock Exchange during the observation period 2014 - 2020. The research sample in this study consists of 7 companies determined by conducting purposive sampling. In this study, uses secondary data from financial statements were reported by construction and building sub-sector companies. Research methods uses descriptive statistics and inferential statistics using the Random Effect Model. The results showed that Leverage and Interest Rate have a significant positive effect, Firm Size has a negative and significant effect. While the Growth and Dividend Policy has no effect on the value of the company.